LITERARY TITLES OF RUSSIAN WRITERS: TYPICAL MODELS AND THEIR SEMANTIC CONVERGENCES (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-141-152The article is devoted to the well-known unofficial titles of Russian writers, which have not yet become the subject of a special research in terms of typological characteristics and semantic similarities. Since the 19th century, the conceptual phrase “unofficial title” of a writer has been used situationally in the works of critics and literary scholars, but none of them gives its definition. Theoretical and methodological approaches have not been developed, and terminological apparatus for studying the problem of titles for writers has not been developed too. The concept of “literary title” acquires definitions in the context of mythologization in the national consciousness of the “cult figure” of the writer. It is argued that the informal status title of a writer is rooted in his literary reputation. The incorporation of his name and works into the national literary canon contributes to the apparition of the cult of the writer, which leads to the apparition of the well-known unofficial title of writer, which characterizes his significance for the nation in a compressed form. Unlike official honorary titles, informal literary titles, expressed by both figurative and non-figurative definitions, denote the justified creative merits (significance) of the titled person. It is proved that, in accordance with the established tradition, the semantic content of commonly used informal titles directly or indirectly contains an indication of the primacy of writers in literature (or another of its fields), which is due to their creative exclusivity, genius, which gives rise to a national “cult”. The author of the article comes to the conclusion that the semantic meaning of primacy in literature underlies the semantic convergence of typical models of commonly used unofficial titles of Russian writers, which distinguishes them from the well-known names-nicknames of writers and formula-stereotypes.Key words: periphrasis, mythologization, literary title, literary nickname, literary canon, literary reputation, formula-stereotype